Knowledge effect on firm performance in manufacturing and service firms - Macau, Flávio Romero (2010)
This thesis seeks to examine the difference between manufacturing and service firms with respect to the effects of knowledge on performance, and the influence of market turbulence in this relationship. Empirical data, resulting from a survey, was collected from more than 1,206 firms, involving several sectors. Two samples were analyzed, one with 334 manufacturing and other with 509 service firms. The findings indicate no significant difference in the importance of knowledge on performance between these sectors in the absence of market turbulence: knowledge development (KD) has a stronger effect than culture of competitiveness (CC) on firm performance. However, under market turbulence, manufacturers differ from service providers. The positive effect of KD is enhanced, while the positive effect of CC remains the same for manufacturing firms. On the other hand, the positive effect of KD is diminished, while the positive effect of CC is enhanced for service firms. This supports the argument concerning differences in the nature of manufacturing and service industries. From a managerial point of view, results confirm the importance of knowledge, irrespective of firm sector or market turbulence. However, while industrial firms should center efforts on KD, service firms must find a balance where knowledge development (e.g. norms, processes, routines) does not impair their culture of competitiveness (e.g. learning, innovation, action). The thesis contributes to existing literature by proposing that: (1) the positive effect of knowledge on performance is confirmed; (2) under turbulent markets manufacturing and service firms have different responses concerning the influence of knowledge on performance; (3) a multidimensional performance construct based on cost, profitability, and growth is an interesting way to evaluate firm sustained competitive advantage, rather than one-dimensional constructs; (4) the CC x KD interaction, found relevant for supply chains in previous studies, is not supported for firms; (5) differences in unit of analysis, e.g. from supply chains to firms, result in different effects of KD and CC on firm performance; (6) existing scales can be improved with the addition of more diverse indicators, capturing a wider range of concepts (e.g. information transfer measurement); and (7) results from previous studies are supported for Brazilian firms, contributing for theory generalization.